TGF-β signaling orchestrates cancer-associated fibroblasts in the tumor microenvironment of human hepatocellular carcinoma: unveiling insights and clinical significance - Junwei Ge; Hongwei Jiang; Junjun Chen; Xuemin Chen; Yue Zhang; Liangrong Shi; Xiao Zheng; Jingting Jiang; Lujun Chen (BMC Cancer)
Abstract Liver cancer, specifically hepatocellular carcinoma (HCC), stands out as one of the most formidable solid tumors, characterized by a dauntingly low survival rate. At the forefront of the tumor microenvironment (TME) orchestrating the initiation and advancement of HCC are cancer-associated fibroblasts (CAFs). TGF-β, widely recognized as a potent activator of CAFs, not only regulates their activity but also assumes a pivotal role in the metastatic journey of the tumor. In our recent study, drawing from the GEO database, we identified two fibroblast subtypes in HCC through single-cell RNA sequencing (scRNA-seq) and explore the expression and distribution of TGF-β and its receptors in the TME of HCC. Subsequently, we investigated the interactions between tumor cells expressing high levels (TGFB1high) and low levels (TGFB1low) of TGF-β in the HCC TME and the two subtypes of CAFs. We also employed multi-color immunohistochemistry (mIHC) technology to examine the expressions of FAP, α-SMA, CD4, Foxp3, and TGF-β in HCC tissues within a tissue microarray. Additionally, we analyzed clinical associations, prognostic values, and the correlation of these molecules. These insights advance our understanding of the molecular mechanisms driving HCC progression and underscore the intricate interplay between tumor cells and the stromal components of the TME.